Understanding Indonesia's BRICS Membership from Role Theory: - - Nugraha, aryanta; Madu, Ludiro; Mulyanto, Indro Herry (Jurnal Paradigma, 2026)
President Prabowo’s decision to pursue full membership in BRICS marks a strategic departure from the cautious stance of former President Joko Widodo, who in 2023 hesitated over concerns that such a move might compromise Indonesia’s Free and Active foreign policy. This paper explores why Indonesia, a country that traditionally committed to non-alignment and ASEAN centrality, becomes a member in a forum often perceived a counterbalance to the Western-led international order. This raises question, what motivated Indonesia in formally entering into BRICS grouping. Employing Role Theory, the paper argues that Indonesia's bid reflects a strategic effort to assert its role as an independent "Bridge Builder" and "Voice for the Global South." It further argues that ambition is complicated by challenges that could potentially strain Indonesia's leadership within ASEAN and its relationship with Western partners. The study employs qualitative content analysis of primary sources, including presidential speeches and media discourse. The findings reveal that Indonesia's entry into BRICS is a test of its ability to navigate competing roles within a polarised international system, underscoring the relevance of role theory in understanding emerging middle powers in multilateralism.